Darunavir and Dolutegravir Combination Therapy in ART experienced HIV-infected Patients: A Preliminary Report. (4th October 2017) - Stang, Alexandra; Perry, Tracy; Fadul, Nada
Abstract: Background: Patients with HIV may require change in therapy for simplification, salvage, or to avoid side effects. There is limited data on the use of dolutegravir (DTG) and ritonavir- or cobicistat-boosted darunvair (DRV) combination therapy alone or with additional active agents in patients with HIV. The objectives of this study were to describe the current use and indications of DTG/DRV combination and to evaluate its effectiveness on viral load suppression (VLS). Methods: A retrospective chart review of HIV-infected patients, 18 years or older, seen at our clinic between August 2013 and December 2015 who were on DRV/DTG combination alone or with additional active agents was conducted. Demographic, clinical, and laboratory information was collected. Descriptive statistics were used for data analysis. Results: Eighty-seven patients were included in the study: 64 (74%) on DRV/DTG alone and 23 (26%) on DRV/DTG plus additional agents. Mean age was 49.3 (18–79); 29 (33.3%) were female; and 77 (89%) were black. Coronary artery disease (CAD) or CAD equivalent was present in 27 (31%), chronic kidney disease in 24 (28%), and chronic hepatitis B infection in 3 (3%) patients. The majority 86 (99%) of patients were treatment experienced; 60 (69%) had been treated with 3 or more antiretroviral drug classes; 57 (66%) were integrase experienced, including 6 (6.9%) with baseline integrase resistance. Baseline HIV viral load was >200 copies/mL in 41 (47%); and CD4 count was <200 in 29 (33%) patients. Reason for switch was reported as salvage in 42 patients (48%) simplification in 33 patients (38%), renal impairment in 11 patients (13%), and other in 6 patients (7%). VLS was achieved or maintained in 40 of 46 patients (87%) who presented for follow up at 6–8 weeks, 25 of 28 (89%) at 3–4 months, 35 of 41 (85%) at 5–6 months, and 55 of 61 (90%) at 7–12 months after starting therapy. Six patients were later switched off of DRV/DTG to another combination, of whom only two required switch due to intolerance (rash in 1 and large pill size in 1). Conclusion: Our preliminary results suggest that darunavir/dolutegravir combination is a viable switch option in HIV patients with the majority of patients achieving or maintaining VLS at 1 year of follow up and only 2 patients required a regimen change due to intolerance. Disclosures: All authors: No reported disclosures.